Depresión y consumo de alcohol en internos rotativos de medicina de la Universidad Nacional de Loja - Loayza Carrión, Tania Valeria (2023)
Depression and alcohol are responsible for high rates of morbidity and mortality worldwide constituting real public health problems which maintain a complex and intricate relationship. Health personnel are a particularly affected group, and for this reason, this research was proposed whose objectives were to characterize according to sociodemographic variables, establish the level of depression, identify the risk of alcohol consumption, and relate the level of depression and the risk of alcohol consumption in rotating medical interns of the National University of Loja. The research was of a quantitative type with an analytical, cross-sectional design and prospective vision. The study included the participation of 80 rotating medical interns who worked at the Isidro Ayora General Hospital and the Manuel Ignacio Monteros General Hospital from September to March 2023. Sociodemographic data were collected, and the Beck Depression Inventory and the Identification Test for disorders due to alcohol consumption were applied, determining that there was a high prevalence of moderate depression (55.0%) and a medium risk of alcohol consumption (60.0%) in participants. Likewise, a statistically significant correlation was found between the level of depression and the risk of alcohol consumption (p<0,05). To sum up, there is a relationship between depression and alcohol consumption in rotating medical interns at the National University of Loja, which requires intervention measures